"I looked it up and you'll probably be fine": cancer survivors' perceptions of helpful and unhelpful support messages and sources. Issue 4 (8th August 2022) - Wanzer, Melissa Bekelja; Czapla, Jennifer
ABSTRACT: This study replicated and extended existing research on cancer survivors' perceptions of helpful and unhelpful social support messages and sources. Forty-three participants with diverse cancer experiences were interviewed about their perceptions of helpful and unhelpful social support messages and sources. Participants recalled six categories of helpful (i.e., network, emotional, esteem, tangible, informational and unspecified) and five categories of unhelpful (i.e., network, emotional, esteem, tangible, informational) messages/sources received during and after cancer treatment. Helpful and unhelpful messages came from spouses, family members, friends, coworkers, healthcare providers and others. Patterns of meaningful message-source combinations are described. Participants recalled double the amount of helpful support messages than nonsupport messages, offering support for the positivity bias. Participants' memories of helpful support messages and sources during treatment followed a consistent pattern; however, expectations and experiences of received social support after completion of cancer treatment were inconsistent and contradictory.